Pelvic index in examinees of macedonian nationality - Janevski, Georgi; Nakeva-Janevska, Natasha; Janevski, Petar; Bojadzieva Biljana; Matveeva, Niki (My University, 2013)
The aim of this study was to monitor the development of the pelvic parameters during puberty and adolescence in exartiinces of both. Material and methods: The measurements were made according to IBP on 1400 examiinees of Macedonian nationality, dlvided into 14 groups. Pelvic index and ndex of pelvic - Vallo's width were calculated. Results: Pelvic index 18-19.5 (moderate width) was found in female examinees aged 14 10 20 years. In males younger than 17 years pelvic index was smaller than 15.9, which indicates a relatively narrow pelvis. Mean value of pelvic index was found in 15-year-old females Conclusion: The analysis of pelvic Indexes in examinees of Macedonian nationality showed that the width of the pelvis was a sexually connected characteristic. A relatively moderate width of pelvis was found in females older than 14 years, which is a secondary sexual daracteristic policinders skorn: The analysis of per vederate with of pelvis.